1964
DOI: 10.1901/jeab.1964.7-69
|View full text |Cite
|
Sign up to set email alerts
|

Adjusting Fixed‐ratio Schedules in the Squirrel Monkey

Abstract: On an adjusting schedule of reinforcement, a parameter of the schedule is varied as a function of some characteristic of the animal's performance. In Experiment I, the fixed-ratio response requirement was varied as a function of the time that elapsed before the animal started responding in each fixed-ratio (initial pause). When initial pauses were shorter than a specified duration, the response requirement was increased; when they were longer than the specified duration, the response requirement was decreased.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

1966
1966
2001
2001

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 9 publications
2
20
0
Order By: Relevance
“…Other than the pairing opera- There are two possible explanations of why the pause-and-run pattern was not always observed. First, the pre-ratio pause is a function of fixed-ratio size (Felton and Lyon, 1966;Ferster and Skinner, 1957 The present results agree with those of Ferster and Skinner (1957), Kelleher, et al, (1964), Neuringer and Chung (1967), Staddon and Innis (1969), and Zimmerman (1960) in that patterning can be engendered within components due to the presentation of a stimulus not paired with food. In the above mentioned studies in which nonpaired stimuli were used, the effects of nonpaired and paired stimuli were not compared.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Other than the pairing opera- There are two possible explanations of why the pause-and-run pattern was not always observed. First, the pre-ratio pause is a function of fixed-ratio size (Felton and Lyon, 1966;Ferster and Skinner, 1957 The present results agree with those of Ferster and Skinner (1957), Kelleher, et al, (1964), Neuringer and Chung (1967), Staddon and Innis (1969), and Zimmerman (1960) in that patterning can be engendered within components due to the presentation of a stimulus not paired with food. In the above mentioned studies in which nonpaired stimuli were used, the effects of nonpaired and paired stimuli were not compared.…”
Section: Resultssupporting
confidence: 85%
“…The results of research on pairing have been equivocal to date. One group of experiments has demonstrated effects on response rates and patterning within components when a stimulus not paired with food accompanied completion of schedule components (Ferster and Skinner, 1957;Kelleher, Fry, and Cook, 1964;Neuringer and Chung, 1967;Zimmerman, 1960). Unfortunately, though effects of a nonpaired stimulus in controlling appropriate schedule performance have been demonstrated, a comparison of the effects of pairing and nonpairing operations was not made in the above mentioned experiments.…”
Section: Introduction General Methods Part Imentioning
confidence: 99%
“…Byrd and Marr (1969), de Lorge (1967), Kelleher (1966), Staddon (1972), Staddon and Innis (1969), Stubbs (1969), and the present Experiment I used stimuli ranging from 0.5 sec to 4 sec in duration and failed to obtain the same behavior as when intervals ended with food presentation. Stubbs (1971) Kelleher, Fry, and Cook (1964) and Zeiler (1970) followed some ratios with a brief stimulus that was never correlated with food, responding did not differ noticeably depending on whether a ratio ended with these events or with food. Since, in addition, Neuringer and Chung observed identical behavior when they substituted a fixed-ratio for the fixedinterval schedule, it does seem possible that their findings characterize fixed-ratio-like performance.…”
Section: Discussionmentioning
confidence: 88%
“…But the generality extends to another response class as well. Findley (1962) and Kelleher, Fry, and Cook (1964) showed that differential reinforcement of the duration of the pause before the first response emitted on fixed-ratio schedules operated in the same way. Differential reinforcement of a property appears to control whatever response is specified independent of the size of the response or whether it involves emitting or withholding a specified response.…”
Section: -20pmentioning
confidence: 93%